Psalm 51: "Take not your Holy Spirit away from me" - L. P. Maré (Acta Theologica)
Even a cursory reading of the New Testament makes one aware of numerous references to the Holy Spirit. The New Testament is thus normally the focus for studies on pneumatology. However, there are many references to jwr in the Old Testament of which 107 refer to God’s activities in nature and in the lives of human beings. In these passages jwr is translated as “spirit”, indicating the   work of the Spirit of God. Pentecostals believe that the presence of the Spirit of God in the lives of believers during the Old Testament period was sporadic and temporary. It was only after the outpouring of God’s Spirit on the Day of Pentecost that the Spirit came to dwell permanently within believers. This article challenges that assumption by analysing Psalm 51. Such analysis reveals that the Spirit of God lived permanently in the life of an Old Testament believer, and ascertains the role of the Spirit of God in the life of the worshipper.